Is the Rising Services Sector in the People's Republic of China leading to Cost Disease? - Duo Qin (Asian Development Bank (ADB), 2004)
The focal issue of this investigation is whether the rising services sector would contract cost disease and stagnate economic growth in People's Republic of China (PRC), as diagnosed generally of tertiarization in Baumol's unbalanced growth model. Using provincial panel data for 1985-2001, the paper examines how labor productivity of the services sector has been associated with GDP growth and whether the services sector has shown signs of cost disease. The key findings are: the currently positive contribution of the services sector to growth is largely due to shifts of labor from agriculture into services; however, signs of cost disease are discernible from demand for service products, wage determination, and labor input demand of the services sector.
hdl:11540/1907
Keywords: 330; Dienstleistungssektor; Arbeitsproduktivität; Arbeitskosten; China